Environment and Religion in Ancient and Coptic Egypt Proceedings of the 1st Egyptological Conference of the Hellenic Institute of Egyptology: 1-3 February 2017. - Maravelia, Alicia (Archaeopress Egyptology Ser., 2020)
Proceedings of a conference held in Athens in 2017, this volume presents 34 fresh and original papers (plus 2 abstracts) on ancient Egyptian religion, environment and the cosmos. Papers connect many interdisciplinary approaches including Egyptology, archaeology, archaeoastronomy, geography, botany, zoology, ornithology, theology and history.